Peranan Kepala Desa Dalam Meningkatkan Efektivitas Pelayanan Publik (suatu Studi di Desa Pinabetengan Selatan Kecamatan Tompaso Barat Kabupaten Minahasa) Kristiana Purba - Purba, Kristiana; Lengkong, Florence Daicy; Laloma, Alden (Sam Ratulangi University, 2015)
ABSTRACT : Background: In the framework of the implementation of Law No. 32 Year 2004 on Regional Government and Law No. 25 of 2009 concerning public services provided to the public, the government as service providers are required to provide excellent service to the community. Excellent public services can be assessed from the process and product services. Aspects of the human resources of the process include, mechanisms and facilities used in the process. While aspects of the product services on the type, quality, and service product kuantits. Dynamic society has evolved in a variety of activities that increasingly require professional government apparatus. Along with the dynamics of society and its development, the need for increasingly complex services as well as better service, fast and precise and able to provide good service to the community. Research Methodology: This study uses descriptive research through in-depth interviews to 19 informants, observation, and document search aided by additional instruments such as interview guides and stationery. Results: Based on the duties and functions of the village chief and public services according to Lanvine the role of village heads in the services, responsiveness, responsibiliti, accountability and effectiveness of service is quite good, although there are still some problems in improving the effectiveness of services. Conclusion: the role of the village head as a public servant based study in rural South Pinabetengan can say is good enough.Keywords: Head of the village, Effectiveness, Public services.